The Role of Leadership in the Transformation of Local Cultural Values through Community-Based Islamic Education - Supian, Yayan; Jahari, Jaja; Gumilar, Setia; Sadiah, Dewi; Azhar, Muhammad Afif Zakwan (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze the role of leadership in transforming local cultural values through community-based Islamic education in an indigenous community in Indonesia. The research method is a qualitative approach using ethnographic techniques, including participatory observation, in-depth interviews, and documentation. The analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion. The results of the study indicate that customary and religious leadership play a key role in maintaining local cultural values , such as cooperation and deliberation, in line with Islamic teachings. This leadership not only functions as a director in social life but also as a facilitator in the process of internalizing cultural values in society, ensuring that traditions remain alive without sacrificing religious principles. In addition, customary and religious leaders work together to guide the community so that these values are relevant to the modern social and religious context. The implications of this study indicate the importance of community-based Islamic education as an effective means to maintain and transform local culture, as well as the need to strengthen the leadership capacity within indigenous communities to manage cultural change. These findings contribute to the development of community-based Islamic education theory and the relevance of local cultural values in the era of globalization.